Perancangan User Experience Aplikasi Edukasi Kondisi Kejiwaan (Sadar Mental Illness) dan Penanganannya Menggunakan Metode Human Centered Design - Annisa Novy Kholiyanti; Hanifah Muslimah Az-Zahra; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Mental Illnesses are health conditions involving changes in emotion that affect everyday life, where the sufferer has difficulty knowing whether the behavior is normal or not, this mental illness is quite dangerous and can lead to suicide. Suicide is the third leading cause of death in the world in adolescents resulting in approximately 4,600 people dead each year. Anxiety disorder is one of mental illness. College life is an ideal place to identify mental illness. However, the mental health of college students has not received special attention so that it is difficult to detect. The growing bad stigma also affects college student reluctance to check up their mental health. Therefore, it is necessary to have an application that can educate college students to care about their mental health so as to avoid the bad effects of mental illness. This research aims to design an educational application for mental conditions with a good user experience so that it is expected to provide easy information regarding the mental health conditions of college students. The method used in this research is human centered design for approach. In this research the evaluation of the solution design used the heuristic evaluation method which involved 3 experts as the evaluator. From the evaluation results, it is found that 9 problems have been sorted based on the highest severity ratings. Where the problems that have the highest severity ratings have high repair priority with errors that must be corrected. Thus the results obtained from this study are application designs in the form of prototypes and design results of application improvements.